2022
DOI: 10.3390/universe8120628
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Spin Period and Magnetic Field of the Crab Pulsar: Decay of the Braking Index by the Particle Wind Flow Torque

Abstract: The evolutions of a neutron star’s rotation and magnetic field (B-field) have remained unsolved puzzles for over half a century. We ascribe the rotational braking torques of pulsar to both components, the standard magnetic dipole radiation (MDR) and particle wind flow (MDR + Wind, hereafter named MDRW), which we apply to the Crab pulsar (B0531 + 21), the only source with a known age and long-term continuous monitoring by radio telescope. Based on the above presumed simple spin-down torques, we obtain the exact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 129 publications
0
9
0
Order By: Relevance
“…In fact, our data also showed ∼33 Hz pulses in Crab (Sikdar et al 2023c) whenever it was observed. We also determined the luminosity of the Crab X-rays, which is much less than the observed luminosity of approximately 1.3 × 10 38 , which is 26% of the total luminosity of the Crab pulsar (Zhang et al 2022). As said previously, our main instrument is an X-ray detector.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our data also showed ∼33 Hz pulses in Crab (Sikdar et al 2023c) whenever it was observed. We also determined the luminosity of the Crab X-rays, which is much less than the observed luminosity of approximately 1.3 × 10 38 , which is 26% of the total luminosity of the Crab pulsar (Zhang et al 2022). As said previously, our main instrument is an X-ray detector.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous alternative explanations exist for the observed low braking indices in young pulsars [63]. Effects due to changes in the moment of inertia of pulsars with superfluid cores [64], magnetic field evolution [65][66][67][68][69][70], modifications to modeling the magnetosphere [71,72], torque from particle wind flows [32,44,73], and internal damping of oscillations in wobbling pulsars [74] are among the notable examples.…”
Section: Jcap05(2024)052mentioning
confidence: 99%
“…For convenience, the following parameters are defined, d=Ldfalse/trueE˙;f=Lffalse/trueE˙$$ d={L}_d/\dot{E};f={L}_f/\dot{E} $$, and d+f=1$$ d+f=1 $$ is satisfied. By the definition of the braking index n=normalΩtrueΩ¨trueΩ˙2$$ n=\frac{\Omega \ddot{\Omega}}{{\dot{\Omega}}^2} $$, the following expression can be derived n=2d+1=32f$$ n=2d+1=3-2f $$, that is, d=(n1)false/2;0.2emf=(3n)false/2$$ d=\left(n-1\right)/2;f=\left(3-n\right)/2 $$ (Zhang et al 2022a).…”
Section: On the Mdrw Modelmentioning
confidence: 99%
“…Now that the MDRW model has been successfully applied to the Crab pulsar (Zhang et al 2022a), however, the difference between the Vela and Crab pulsars is that the real age of the Vela pulsar is unknown, and its braking index is very low, close to 1.4 (2.5 for the Crab pulsar), which has a big deviation from the braking index 3 predicted by MDR model. When the pulsar's braking index is very low, the MDR model cannot be applied to predict its spin period evolution, and even when it evolves to a long period, the spin‐down is mainly dominated by the wind flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation